NOMMENSEN'S DIALOGICAL APPROACH: THE APPROPRIATION OF THE BIBLICAL CONCEPT OF "LOVE YOUR GOD AND LOVE YOUR NEIGHBORS" IN BATAK TOBA COMMUNITIES - Jack Kawira (Verbum Christi: Jurnal Teologi Reformed Injili, 2018)
Nommensen's missionary work is an outstanding act of intercultural and dialogical evangelism. His eagerness to learn Batak Toba people's culture and language shaped his cultural sensitivity in evangelism and made his missionary work successful. The biblical concept of "love your God and love your neighbor" in Nommensen will be examined and compared with Batak Toba people's understanding in four dimensions of belief, sense of belonging, behavior, and experience. Afterwards, how Nommensen's dialogical approach appropriates this concept in Batak Toba communities who constantly live at war will be examined.KEYWORDS: dialogical; appropriation; love; evangelization; culture.